In vitro characterization of neonatal, juvenile, and adult porcine islet oxygen demand, β‐cell function, and transcriptomes. (27th July 2018) - Smith, Kate E.; Purvis, William G.; Davis, Melissa A.; Min, Catherine G.; Cooksey, Amanda M.; Weber, Craig S.; Jandova, Jana; Price, Nicholas D.; Molano, Diana S.; Stanton, James Brett; Kelly, Amy C.; Steyn, Leah V.; et al.
Abstract: Background: There is currently a shortage of human donor pancreata which limits the broad application of islet transplantation as a treatment for type 1 diabetes. Porcine islets have demonstrated potential as an alternative source, but a study evaluating islets from different donor ages under unified protocols has yet to be conducted. Methods: Neonatal porcine islets (NPI; 1‐3 days), juvenile porcine islets (JPI; 18‐21 days), and adult porcine islets (API; 2+ years) were compared in vitro, including assessments of oxygen consumption rate, membrane integrity determined by FDA/PI staining, β‐cell proliferation, dynamic glucose‐stimulated insulin secretion, and RNA sequencing. Results: Oxygen consumption rate normalized to DNA was not significantly different between ages. Membrane integrity was age dependent, and API had the highest percentage of intact cells. API also had the highest glucose‐stimulated insulin secretion response during a dynamic insulin secretion assay and had 50‐fold higher total insulin content compared to NPI and JPI. NPI and JPI had similar glucose responsiveness, β‐cell percentage, and β‐cell proliferation rate. Transcriptome analysis was consistent with physiological assessments. API transcriptomes were enriched for cellular metabolic and insulin secretory pathways, while NPI exhibited higher expression of genes associated with proliferation. Conclusions: The oxygen demand, membrane integrity, β‐cell function and proliferation, and transcriptomes of islets from API, JPI, and NPI provide a comprehensive physiological comparison for future studies. These assessments will inform the optimal application of each age of porcine islet to expand the availability of islet transplantation.